Effect of alkaline treatment on structural characterisation, thermal degradation and water absorption ability of coir fibre polymer composites - Yew, Been Seok; Martini Muhamad,; Saiful Bahri Mohamed,; Wee, Fwen Hoon (Penerbit Universiti Kebangsaan Malaysia, 2019)
The alkaline treatment with 5 wt. % sodium hydroxide (NaOH) solution at room temperature for 24 and 48 h was performed on coir fibre. The structural characterisation, thermal degradation and water absorption ability of the untreated and NaOH-treated coir fibre polymer composites have been studied. Scanning electron microscope (SEM) images showed that coir fibres treated with NaOH have rough surface texture and the roughness of the fibre surface becomes significant as the duration of the NaOH treatment increased. Fourier transform infrared (FTIR) spectra confirmed that NaOH treatment removed hemicelluloses as evidenced by the absence of absorption bands at 1724.36 cm-1 and changes the absorption intensity at bands 1244.09 cm-1and 1249.87 cm-1 due to the loss of lignin. NaOH-treated coir fibre composites demonstrated better thermal stability at low temperature degradation. At high temperature, the thermal stability was reduced due to the decreased of residual lignin content. The water absorption of the NaOH-treated coir fibre composites was lower than untreated coir composite contributed by better interfacial adhesion between the NaOH-treated coir fibre to epoxy resin.